Effects of problem-based learning on cognitive, affective and communication skills in learning pediatric nursing among undergraduates in Islamic Azad University, Iran - Salari, Mohsen (2016)
The nursing profession is faced with new challenges which necessitate the implementation of new and more effective educational strategies in order to enhance nurses and nursing trainees' essential competencies to cope with challenges effectively. A quasi-experimental, posttest-control group design with nonequivalent groups was conducted to investigate the effects of Problem-Based Learning on cognitive, affective, and communication skills in learning Pediatric Nursing among university students. The subjects of the study were undergraduate students who enrolled in Pediatric Nursing II course at Islamic Azad University in Iran. The experiment was conducted over a period of eight weeks, in which the nursing students met weekly over duration of one two-hour session and two two-hour sessions. In this study, two experimental groups, namely the Traditional Problem-Based Learning (TPBL) and the Hybrid Problem- Based Learning (HPBL), and one Conventional Teaching and Learning (COTL) group were involved. The TPBL group underwent learning using the traditional problem-based learning approach with guided questions and a tutor; and the HPBL group underwent learning using problem-based learning approach with minimal lecturing, guided questions and a tutor. The COTL group underwent learning using conventional instruction utilizing full lecture. The three groups were compared on cognitive and affective performances, namely, overall nursing performance, mental effort, instructional efficiency, metacognitive awareness, motivation towards learning, and also, communication skills. Five instruments were used in this study, namely Pediatric Nursing Performance Test, Paas Mental Effort Rating Scale, Metacognitive Awareness Inventory, Instructional Materials Motivation Survey, and also, Communication Skill Checklist. The statistical analyses utilized were ANOVA, ANCOVA, and mixed between-within subjects ANOVA. Findings of this study showed that the TPBL and HPBL instructional strategy in comparison with COTL enhanced students’ overall performance in Pediatric Nursing, higher-order questions performance, and induced higher level of metacognitive awareness, communication skills, instructional efficiency and motivation toward learning with less mental effort invested during the learning. These findings indicated that the TPBL and HPBL are superior in comparison to the conventional instruction, hence implying that integrating the use of these approaches in teaching and learning of Pediatric Nursing lends higher efficiency than the conventional strategy. Therefore, it may be concluded that both forms of PBL were effective for student learning of Pediatric Nursing and also that PBL may be useful where there are shortages of instructors or faculty members in handling teaching and learning.